ANALISIS PERSEPSI PETANI KELAPA SAWIT POLA SWADAYA MENGHADAPI SERTIFIKASI RSPO DI KECAMATAN UKUI KABUPATEN PELALAWAN - Harianja, Kriston; Hutabarat, Sakti; Dewi, Novia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Oil palm plays an important role in Indonesian economy. Development of palm oil supply chain creates a large number of employment, reduces poverty, increases foreign exchange earnings, and improves rural welfare. However, oil palm expansion has been claimed to be the source of deforestation, biodiversity loss, GHG emision, land and forest fires and land conflicts. Some private and non-governmental organizations have established a certification system, âthe Roundtable on Sustainable Palm Oilâ, to mitigate the negative impacts of oil palm production. All oil palm growers have to comply with the Principle and Criteria of RSPO to be included in the global market. However, the smallholders are the most vulnerable party to meet the standard because of their limited access to various inputs, finance, and information. Certification is a new challenge for smallholders in a global oil palm supply chain. The objective of this study is to analyse farmersâ perception on RSPO certification. This research use the likert scale to measure farmersâ perception. The data were collected through a survey on the farmers. The size of sample selected from the population are 59 independent smallholders. The result shows that the farmersâ perception on certification is âvery goodâ. There are an increasing awareness of the farmers on sustainable oil palm production. The study also found that most of the farmers participate in the process of certification. However, the implementation of the Principles and Criteria carried out by oil palm growers is still below the certification standard i.e., only 65,45%. Keywords : Oil palm, Perception, RSPO and independent smallholder.